The Effect of Multimedia Usage on EFL Learners' Improvement in Conversational Listening Skill at University Level - Tahsin Hussein Rassul; Hussein Ali Wali (Zanco Journal of Humanity Sciences)
The current research is experimental which tries to investigate the EFL tertiary learners’ development level of the conversational listening skill through using multimedia materials depending on quantitative data collection and analysis.